POLA INTERAKSI KELOMPOK NELAYAN DALAM MENINGKATKAN TARAF HIDUP DI DESA TELUK KECAMATAN LABUAN KABUPATEN PANDEGLANG - Meli Oktaviana (Prodi Tadris Ilmu Pengetahuan Sosial FITK UIN Sumatera Utara Medan, 2023)
This study aims to determine the pattern of interaction of fishermen groups in improving living standards in Teluk Village, Labuan Subdistrict, Pandeglang Regency. This research took place in Teluk Village, Labuan Sub-district, Pandeglang Regency. In this study, researchers used qualitative methods with a qualitative descriptive approach. Data collection by means of observation, in-depth free interviews. The results of the study found that a lot of efforts have been made by the fishing community in Teluk Village to improve the standard of living that is expected to be very difficult to realize. This is due to the difficulties they experience in terms of obtaining capital from the government and having minimal access to fishing so that their lifestyle is very dependent on the patron-client interaction pattern between fishermen, boat owners and middlemen as capital owners.